The effects of fixed-term contracts on workers in colombia (2014)
This paper studies the effects of fixed-term contracts on workers. Specifically,the paper analyzes their impact on wages and on satisfaction levels. Regulationsgoverning fixed-term and indefinite contracts in Colombia and the main laborreforms related to these two types of contract are analyzed. Women, young and low-educated workers, who work in small firms, in the private sector and in constructionor manufacturing are most likely to have fixed-term contracts. In terms of wages,we found a significant raw and adjusted wage gap against workers with fixedtermcontracts. Finally, we found, as expected, evidence that fixed-term contractsreduce the level of worker satisfaction.